Absorption, distribution and accumulation of nitrogen applied at different phenological stages in southern highbush blueberry (Vaccinium corymbosum interspecific hybrid) - Pescie, María A. (2018)
Southern highbush blueberry has an early harvesting and then a long period of vegetative growth until dormancy, compared to highbush and rabbiteye blueberries. Nitrogen requirements could be different because of this specific early harvesting. Absorption of 15N enriched ammonium sulfate was compared at five phenological stages from bud swell to pre-dormancy in two years old plants of the cultivars Star and ÓNeal. Plants grown in pots were irrigated with ammonium sulfate solution (15N). Five plants for each application date were excavated and separated in parts (roots, canes, leaves, flowers, fruits or floral buds). Samples were taken three weeks after application from bud swell to pre-harvest treatment, and three month after for post-harvest and pre-dormancy treatment. Each tissue were dried and weighed before and after, and analyzed for 15N content, N content and N %….N%, and in leaves were also determined macro and micro nutrients. Nitrogen fertilization at bud swell is effective, even for the ÓNeal cultivarthat present floral bud break in absence of leaves. Post-harvest fertilization contribute N for summer vegetativegrowth which would influence the floral buds development next year, Nitrogenstorage at this time would led to the improved floral behavior next year. Nitrogen losses risk is lower at post-harvestfertilization.